A grasp planning algorithm under uneven contact point distribution scenario for space non-cooperative target capture - CAI, Bicheng; YUE, Chengfei; WU, Fan; CHEN, Xueqin; GENG, Yunhai (Chinese journal of aeronautics, 2023)
The contact point configuration should be carefully chosen to ensure a stable capture, especially for the non-cooperative target capture mission using multi-armed spacecraft. In this work scenario, the contact points on the base and on the arms are distributed on the opposite side of the target. Otherwise, large forces will be needed. To cope with this problem, an uneven-oriented distribution union criterion is proposed. The union criterion contains a virtual symmetrical criterion and a geometry criterion. The virtual symmetrical contact point criterion is derived from the proof of the force closure principle using computational geometry to ensure a stable grasp, and the geometry criterion is calculated by the volume of the minimum polyhedron formed by the contact points to get a wide-range distribution. To further accelerate the optimization rate and enhance the global search ability, a line array modeling method and a continuous-discrete global search algorithm are proposed. The line array modeling method reduces the workload of calculating the descent direction and the gradient available, while the continuous-discrete global search algorithm reducing the optimization dimension. Then a highly efficient grasping is achieved and the corresponding contact point is calculated. Finally, an exhaustive verification is conducted to numerically analyze the disturbance resistance ability, and simulation results demonstrate the effectiveness of the proposed algorithms.